Analisis SWOT dalam Pelaksanaan Pengelolaan Tempat Evakuasi Sementara oleh BPBD Kota Padang - Lakosa, Fegi Yani (JESS (Journal of Education on Social Science); Vol 3 No 2 (2019): Special EditionDO - 10.24036/jess/vol3-iss2/187, 2019)
The purpose of this study is to analyze strengths, weaknesses, opportunities, and threats faced by the Padang city BPBD in managing temporary evacuation sites. This type of research is qualitative with descriptive methods. The results of this study indicate that the strength of the Regional Disaster Management Agency in the City of Padang in managing this temporary evacuation site is to have a legal basis such as a Decree issued by the Padang BPBD Chief of Management in conducting management, law number 24 of 2007 concerning countermeasures disaster and lau number 28 of 2002 concerning building. As for the Weaknesses faced are human resources and the limited budges for managing temporary evacuation sites. Then what becomes an  opportunity is that the existence of the legal basis provides an opportunity to collaboration with other organizations in evaluating the management of temporary evacuations sites. Furthermore, the threat faced is the presence of irresponsible people who take electrical equipment arround the temporary evacuations site